Respuesta :
x - 12y = -210 ---------------------------> x - 12y = -210
x - 6y = 90 ----> Multiply by 2 ---> 2x - 12y = 180
Add together --> 3x + 0y = -30
3x = -30
Divide by 3 ------> x = -10
x - 6y = 90 ----> Multiply by 2 ---> 2x - 12y = 180
Add together --> 3x + 0y = -30
3x = -30
Divide by 3 ------> x = -10
(a): x - 12 y = - 210
(b): x - 6y = 90, multiply (2) by - 1 → (c): -1(x) - (-1)(- 6y) = -1(90)
(c) → -x + 6y = -90
Now add up (a) + (c) ↔ -6y = -300 and y = 50
Plug this value in any of the equation and you'll find x=390
(b): x - 6y = 90, multiply (2) by - 1 → (c): -1(x) - (-1)(- 6y) = -1(90)
(c) → -x + 6y = -90
Now add up (a) + (c) ↔ -6y = -300 and y = 50
Plug this value in any of the equation and you'll find x=390